Investigating the linkage between climate variables and food security in ESA countries - Belloumi, Mounir (International Food Policy Research Institute, 2014)
This paper investigates the effect of climate variables (precipitation and temperature) on food security indicators from 1961-2011 for 10 Eastern and Southern African countries by estimating fixed effects models. Food security is approximated by three indicators: food production index, mortality rate of people under five years of age, and life expectancy at birth. The results show that GDP per capita, inflation, population growth, and land under cereal production are significant in explaining the indicators of food security.